Defense Mechanism to Overcome Anxiety in Violet Evergarden Volume 2 by Kana Akatsuki - Devi Chahyawati; Muhammad Adam; Ulum Jannah (Prologue: Journal on Language and Literature, 2022)
This study aims to analyze the role of Defense Mechanism in reducing the anxiety in the novel Violet Evergarden Volume 2 by Kana Akatsuki. There are two purposes for this research. The first is to identify the type of anxiety in the novel. Second, Defense Mechanism work overcome the anxiety in the novel. The theory used in this research is Sigmund Freud's psychoanalysis, particularly Mechanism Defense and Anxiety. The method used in this research is qualitative descriptive. The researcher found that the factors causing the anxiety were classified into 3 types, namely moral anxiety, realistic anxiety, and neurotic anxiety. To overcome the anxiety, the characters use Ego Defense Mechanism as a form of self-defense. The types of defense mechanisms that the researchers found were suitable for overcoming the anxiety in the novel were Repudiate of Fact, Eradicate the mistakes of the past, Transfer negative emotion into beneficial activity, Dispersion of Negative emotions, and Contradictory behavior. The researcher found that the anxiety felt by the characters came from themselves and others, by using the Defense Mechanism the characters could relieve the anxiety they felt.